PEMIKIRAN HUKUM ISLAM IBNU TAIMIYYAH - Muhammad Syaikhon (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2015)
Ibn Taymiyyah was a reformer and medieval Islamic purifiers who had high authority . His thinking method was SalafÂ  method which was based on the Qur'an and Hadis . The laws of fiqh that he often used leaned to the priest, imam Ahmad ibn Hanbal . Ushul fiqh method or Islamic legal thought of Ibn Taymiyah was Qur'an and Hadis , ijma ' , qiyas , istishab , and mashlahah mursalah .Thoughts of Ibn Taymiyyah can be classified into three types, namely: the same thinking by Imam Ahmad bin Hanbal , thoughts were not characterize a particular schools but according to Ibn Taymiyah 's own thoughts and ideas that are contrary to the opinions of Imam whole Islamic schools .Â